De la campagne écossaise aux milieux aristocratiques londoniens : le déracinement de Thomas Carlyle? - Catherine Heyrendt (Cahiers Victoriens et Edouardiens)
Despite his humble Scottish background, and the rigid Victorian social hierarchy, Thomas Carlyle was able to « write his way up » in the world, and was eventually invited into the highest London circles. Yet both he and his wife failed to acquire a true sense of belonging to their new geographical, social and spiritual environment. Their letters to their families—arguably an attempt to fight gradual estrangement—bear witness to their often disapproving yet compelling fascination with London society. Carlyle’s works, always sincere and never subservient regardless of possible consequences, reflect his uprooted and alien condition.